The clever Gribbles - "Cowley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Asia and Silas invent a rocket-powered skateboard for their brother Fred's birthday. But the neighbours (and Police Sergeant Lisa) are not impressed by the resulting mayhem - or the absence of Mr and Mrs Gribbble. The clever Gribbles need all their ingenuity to prove that they're well looked after by Mrs Munch the cook, Creep the python and Birdie the parrot
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Inventions Children's fiction